The Impact of Powerpoint Animation in Increasing the Students' Listening Skills at Islamic Senior High School - Khoirotun Naimah; Jufriadi Jufriadi; Fadhliyah Rahmah Muin (FOSTER: Journal of English Language Teaching, 2024)
This study centered on utilizing animated PowerPoint presentations as audiovisual aids for enhancing the listening skills of tenth-grade students at Islamic Senior High School of Al-Falah Lemahabang. The study employed a pre-experimental approach, employing pre-test and post-test to evaluate the influence of PowerPoint animation on listening skills among tenth-grade students at Islamic Senior High School of Al-Falah Lemahabang. The sample, comprising 24 students, was selected through random sampling. Both pre-test and post-test scores were optimized as research tools. Examination of the data demonstrated a notable contrast between the pre-test (59.79) and post-test (76.67) outcomes. The paired sample test results yielded a significance value of 0.001, below the threshold of 0.05, prompting the rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). This suggests that employing PowerPoint animation as an audiovisual learning tool effectively enhances listening skills in the context of the Islamic Senior High School of Al-Falah Lemahabang. It means that PowerPoint animation as audiovisual media can increase listening ability in tenth-grade students at Islamic Senior High School of Al-Falah Lemahabang in 2023/2024 academic years.